2015
DOI: 10.1007/s11764-015-0463-x
|View full text |Cite
|
Sign up to set email alerts
|

A study of donepezil in female breast cancer survivors with self-reported cognitive dysfunction 1 to 5 years following adjuvant chemotherapy

Abstract: Purpose Some breast cancer survivors report cognitive difficulties greater than 1 year after chemotherapy. Acetylcholinesterase inhibitors (AChEI) may improve cognitive impairment. We conducted a randomized, placebo-controlled, pilot study to assess the feasibility of using the AChEI, donepezil, to improve subjective and objective measures of cognitive function in breast cancer survivors. Methods Women who received adjuvant chemotherapy 1–5 years prior with current cognitive dysfunction symptoms were randomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
73
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 52 publications
1
73
1
1
Order By: Relevance
“…115,116 Additionally, a study in breast cancer survivors suggested improved verbal memory in those who had poorer cognitive functioning at baseline. 117 Cholinesterase inhibitor studies provide support for the cholinergic system as a therapeutic target for improving cognitive functioning in CRCI. 115117 More selective cholinergic stimulation may potentially be useful for certain cognitive symptoms.…”
Section: Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…115,116 Additionally, a study in breast cancer survivors suggested improved verbal memory in those who had poorer cognitive functioning at baseline. 117 Cholinesterase inhibitor studies provide support for the cholinergic system as a therapeutic target for improving cognitive functioning in CRCI. 115117 More selective cholinergic stimulation may potentially be useful for certain cognitive symptoms.…”
Section: Interventionmentioning
confidence: 99%
“…117 Cholinesterase inhibitor studies provide support for the cholinergic system as a therapeutic target for improving cognitive functioning in CRCI. 115117 More selective cholinergic stimulation may potentially be useful for certain cognitive symptoms. For example, a randomized, placebo-controlled study evaluating the use of transdermal nicotine treatment as a therapeutic strategy for persistent CRCI is currently underway (NCT02312934).…”
Section: Interventionmentioning
confidence: 99%
“…44,7880 Additionally, most intervention studies have included only a small number of patients. These interventions can be grouped into pharmacological and non-pharmacological categories.…”
Section: Research Gapsmentioning
confidence: 99%
“…Examples of pharmacological agents investigated included donepezil, methylphenidate, modafinil and erythropoietin. 78,79,81,82 Non-pharmacological interventions include specific exercise programs and cognitive training. 80,83,84 Selected studies are shown in Table 4.…”
Section: Research Gapsmentioning
confidence: 99%
“…[13] As several studies have shown, memory impairment is the most prominent presentation of chemotherapy-induced cognitive impairment (CICI) in patients with breast cancer, [2,4,5] and acts as an important factor affecting the long-term quality of life in these patients. [6] …”
Section: Introductionmentioning
confidence: 99%